Higher‐Order Human Telomeric G‐Quadruplex DNA Metalloenzymes Enhance Enantioselectivity in the Diels–Alder Reaction. Issue 4 (11th February 2015) - Li, Yinghao; Jia, Guoqing; Wang, Changhao; Cheng, Mingpan; Li, Can
Abstract Short human telomeric (HT) DNA sequences form single G‐quadruplex (G4) units and exhibit structure‐based stereocontrol for a series of reactions. However, for more biologically relevant higher‐order HT G4‐DNAs (beyond a single G4 unit), the catalytic performances are unknown. Here, we found that higher‐order HT G4‐DNA copper metalloenzymes (two or three G4 units) afford remarkably higher enantioselectivity (>90 % ee) and a five‐ to sixfold rate increase, compared to a single G4 unit, for the Diels–Alder reaction. Electron paramagnetic resonance (EPR) and enzymatic kinetic studies revealed that the distinct catalytic function between single and higher‐order G4‐DNA copper metalloenzymes can be attributed to different CuII coordination environments and substrate specificity. Our finding suggests that, like protein enzymes and ribozymes, higher‐order structural organization is crucial for G4‐DNA‐based catalysis.